The Role of Information Technology in Enhancing the Quality of Distance Learning in the Digital Era - Sholihah, Husna Imro'athush; Suhaeb, M. Iqbal; Nugroho, Arief Styo; Mokay, Meggy Merlin; Thalib, Darmawan (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to explore the role of information technology in improving the quality of distance learning in the digital era. This study used qualitative research methods. It gathered data through in-depth interviews with educators and students in Muhammadiyah 2 Depok Junior High School, Jogja with the respondent 10 teachers and 10 Class VIII student. Additionally, it involved document analysis of online learning practices. The results reveal that information technology enhances education accessibility. It also improves learning. It does this by enabling better interaction and using more engaging materials.